Global trends and frontiers of research on pathologic myopia since the millennium: A bibliometric analysis - Yang, Jingyuan; Wu, Shan; Zhang, Chenxi; Yu, Weihong; Dai, Rongping; Chen, Youxin (Frontiers in Public Health, 2022)
Purpose Pathologic myopia (PM) is an international public health issue. This study aimed to analyze the research trends of PM by reporting on publication trends since 2000 and to identify influential journals, countries, authors, and keywords involved in PM. Methods A bibliometric analysis was performed to evaluate global production and development trends in PM since 2000, and keywords involved in PM. Results A total of 1435 publications were retrieved. PM has become an attractive topic (relative research interest, ranging from 0.0018% in 2000 to 0.0044% in 2021) and a global public health issue. China, USA, and Japan were the top three countries with the highest number of publications, and the journals, authors, and institutions that published the most relevant literatures also came from these three countries. China exhibited the most rapid increase in the number of publications (increased from 0 publications in 2000 to 69 publications in 2021). Retina published the most papers on PM. Kyoko Ohno-Matsui and her institution, Tokyo Medical & Dental University, contributed the maximum number of publications among authors and institutions, respectively. Based on keyword analysis, previous research has emphasized myopic choroidal neovascularization and treatment, while recent hotspots included PM changes based on multimodal imaging, treatment, and pathogenesis. Keyword analysis also revealed that deep learning was the latest hotspot and has been applied to the detection of PM. Conclusion Our results can help researchers understand the current status and future trends of PM. China, USA, and Japan have the highest influence, based on the number of publications, top journals, authors, and institutions. Current research of PM highlights the pathogenesis and application of novel technologies, including multimodal imaging and artificial intelligence.